Diseño de un manual de procesos para la obtención de licencias de importación ante agrocalidad - Fajardo Orellana, Elizabeth Susana (2016)
Nowadays, Agroquality counts with a big list of products, which one must fulfill with some requirements phytosanitary in order to obtain the certification emited for this entity then it must be permited to deposit into the country, these requeriments are done previous to the shipment of the charging. The present Project is directed of all the importers and external agent who wants to manage their permissions of phytosanitary imports by fulfilling with the valid rules requiered by the entity infor avoiding payments of penalty fee and possible reshipment of the charging…..